2008
DOI: 10.1017/s0022112008000165
|View full text |Cite
|
Sign up to set email alerts
|

Parametrically forced gravity waves in a circular cylinder and finite-time singularity

Abstract: In this paper we present results on parametrically forced gravity waves in a circular cylinder in the limit of large fluid-depth approximation. The phase diagram that shows the stability-forcing-amplitude threshold and the wave-breaking threshold has been determined in the frequency range of existence of the lowest axisymmetric wave mode. The instability is shown to be supercritical for forcing frequencies at and above the natural frequency and subcritical below in a frequency range where the instability and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 30 publications
6
49
0
1
Order By: Relevance
“…However, the free-surface dynamics are not self-similar and divergent surface tension is not the driving mechanism, as they suggested and was explained by Brenner (2000). See also the follow-up study by Das & Hopfinger (2008) who suggest inertial focusing, but did not have time-resolved imaging to capture the fastest jets. We further verify this by tracking the collapse of the final dimple radius, in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the free-surface dynamics are not self-similar and divergent surface tension is not the driving mechanism, as they suggested and was explained by Brenner (2000). See also the follow-up study by Das & Hopfinger (2008) who suggest inertial focusing, but did not have time-resolved imaging to capture the fastest jets. We further verify this by tracking the collapse of the final dimple radius, in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear what role surface tension and viscosity play, as discussed in Thoroddsen et al (2007b) who showed the focusing of capillary waves on a free-falling drop can generate a fine jet. Das & Hopfinger (2008) have investigated the parametrically forced waves in more detail.…”
Section: Crater Collapse and Singular Jetsmentioning
confidence: 99%
“…In most of these (e.g. Ciliberto & Gollub, 1985;Crawford, Knobloch & Riecke, 1990;Das & Hopfinger, 2008;Batson, Zoueshtiagh & Narayanan, 2013), the interface takes the form of Bessel functions, including axisymmetric modes, while Rajchenbach, Clamond & Leroux (2013) report intriguing patterns of the form of stars and pentagons.…”
Section: Simulation In a Cylindrical Containermentioning
confidence: 99%
“…Douady & Fauve, 1988;Douady, 1990;Simonelli & Gollub, 1989) and cylindrical (e.g. Ciliberto & Gollub, 1985;Das & Hopfinger, 2008;Batson, Zoueshtiagh & Narayanan, 2013;Rajchenbach, Clamond & Leroux, 2013) containers, which have led to important theoretical developments (e.g. Meron, 1987;Silber & Knobloch, 1989;Crawford, Knobloch & Riecke, 1990;Crawford, 1991;Gomes & Stewart, 1994) in the fields of nonlinear physics and pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…When the acceleration exceeds a certain threshold level, referred to threshold acceleration, the stable periodic surface waves are transformed to an unstable aperiodic state and show some upward jets in Figure 13(c). Goodridge et al [14] defined the threshold acceleration as the acceleration level where two droplets are detected within 10 s. Das and Hopfinger [10], however, defined it as a jet forming or wave crest pinching off, followed by irregular motion. In this study, droplets or long filament-like jet formations are assumed as criteria for threshold acceleration because droplet formation itself in numerical studies may result in a different criterion according to grid resolution.…”
Section: Liquid Fuel Surface Stability Under Thrust Oscillationmentioning
confidence: 99%